2007
DOI: 10.1530/rep-06-0281
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoprotein enriched in astrocytes-15 is expressed in mouse testis and protects spermatocytes from apoptosis

Abstract: Phosphoprotein enriched in astrocytes (PEA-15) is a 15 kDa acidic serine-phosphorylated protein expressed in different cell types, especially in the CN. We initially detected the expression of PEA-15 in primary cultures of Sertoli cells. To assess the presence and localization of PEA-15 in the mouse testis, we studied the expression pattern of the PEA-15 protein by immunohistochemistry and mRNA by in situ hybridization. Both the protein and the mRNA of PEA-15 were localized in the cytoplasm of Sertoli cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…It is thus likely that in mammals p63 expression is subject to analogous developmental control mechanisms to those we have observed for C. elegans . While there is no reported evidence that ERK signaling impacts on p63 expression in the mammalian germline, the finding that ERK expression is observed in meiotic prophase in mouse spermatocytes [47], [48] lends weight to the idea that ERK signaling may play a role in regulating apoptosis in the mammalian germline.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus likely that in mammals p63 expression is subject to analogous developmental control mechanisms to those we have observed for C. elegans . While there is no reported evidence that ERK signaling impacts on p63 expression in the mammalian germline, the finding that ERK expression is observed in meiotic prophase in mouse spermatocytes [47], [48] lends weight to the idea that ERK signaling may play a role in regulating apoptosis in the mammalian germline.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have shown that adhesion of germ cells in the seminiferous epithelium is also regulated by the ERK signaling cascade Xia et al, 2006a). ERK, a ANCHORING JUNCTIONS AND MALE CONTRACEPTION nonreceptor protein tyrosine kinase of the mitogen-activated protein (MAP) kinase family, was shown to associate largely with Sertoli cells and spermatocytes in the basal compartment (Mizrak et al, 2007). Weak ERK immunoreactivity was also detected at the apical ectoplasmic specialization between Sertoli cells and early elongating spermatids, but phosphorylated ERK-Thr 202 / Tyr 204 localization was found predominantly between Sertoli cells and spermatids at stage 8 and beyond in the rat Xia and Cheng, 2005).…”
Section: Phosphatases and Kinasesmentioning
confidence: 99%
“…As such, phosphorylated ERK has been hypothesized to mediate restructuring of the apical ectoplasmic specialization, and to regulate spermatid movement and release. Note that the localization patterns of ERK and phosphorylated ERK-Thr 202 /Tyr 204 Mizrak et al, 2007) are remarkably similar to the localization patterns of FAK and phosphorylated FAK-Tyr 397 , because the immunoreactivity of FAK was also restricted largely to the blood-testis barrier but that of phosphorylated FAK-Tyr 397 was restricted to the apical ectoplasmic specialization (Siu et al, 2003). These results seemingly suggest that two forms of a specific protein kinase (i.e., phosphorylated and unphosphorylated) are needed to regulate closely related cellular functions in Sertoli cells, such as junction restructuring that occurs at the apical ectoplasmic specialization and blood-testis barrier, which are present at opposite ends of the Sertoli cell.…”
Section: Phosphatases and Kinasesmentioning
confidence: 99%
“…The testes were then dissected and the epididymes removed. After the testes were weighed, they were immersion fixed in Bouin's solution, paraffin embedded, sectioned, and either stained with periodic acid-Schiff-hematoxylin or processed for terminal deoxynucleotidyl transferase-mediated deoxyuridine 5-triphosphate-biotin nick end labeling (TUNEL) to specifically monitor apoptosis of the germ cells, as described elsewhere (19). For the last, testis sections were boiled for 5 minutes in 10 mM citric buffer (pH 6.0) at 98 C and slowly were cooled to room temperature.…”
mentioning
confidence: 99%